Modeling of Water Surface Elevation Using MIKE 21 Based on Rupat Strait Bathymetric Data - Ahmad, Alianisa; Mubarak, Mubarak; Tanjung, Afrizal; Rifardi, Rifardi; Ilahi, Ilham (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
The Rupat Strait, a strategically crucial marine channel separating Sumatra Island from Rupat Island, exhibits complex hydrodynamic characteristics influenced by tidal propagation from the adjacent Malacca Strait. As a vital shipping corridor, the strait's navigational safety is fundamentally governed by its bathymetric profile and tidal regime. This study implements an integrated methodological framework combining in situ bathymetric surveys with MIKE 21 hydrodynamic modeling to assess morphological dynamics quantitatively. Systematic validation of model outputs against field measurements revealed significant spatial variations in seafloor topography, including pronounced shallowing (>6.6 m) and substantial deepening (≤17 m) at distinct locations. Concurrent analysis of tidal data demonstrated extreme water level fluctuations, ranging from -2.36 m during the lowest astronomical tides to +6.28 m during peak tidal surges. These geomorphological alterations appear correlated with anthropogenic pressures, particularly intensive shipping traffic and coastal zone modifications, suggesting a coupled natural-anthropogenic forcing mechanism governing the strait's evolving morphodynamics. The findings highlight the critical need for ongoing monitoring to ensure maritime safety and sustainable coastal management in this rapidly changing marine environment